Atividade antifúngica das crotalicidinas contra leveduras resistentes e caracterização do mecanismo de ação do fragmento Ctn[15-34] com modelos de biomembranas - Aguiar, Francisca Lidiane Linhares de (2019)
Crotalicidin (Ctn), a cathelicidin-related antimicrobial peptide from the venom gland of a South American rattlesnake, as well as its C-terminal Ctn[15-34] fragment, have shown important activities against micro-organisms, trypanosomatid protozoa and certain lines of tumor cells. Herein, the activity against clinical strains of fluconazoleresistant Candida albicans and of amphotericin B and fluconazole-resistant Cryptococcus spp. is demonstrated. Microdilution and luminescent cell viability tests were used to evaluate and compare the susceptibility of pathogenic yeasts and the inhibitory potential of these peptides. The time-kill curves of the most active peptide (Ctn[15-34]) alone or in combination with fluconazole against resistant pathogenic yeasts were determined. Concomitantly, fungicidal and/or fungistatic effect of Ctn[15- 34] were visualized by the spotting test. Viability tests using XTT, confocal laser scanning microscope and AFM were used to determine antibiofilm activity of Ctn[15- 34] against C. albicans. Fluorescence assays using Di-8-ANEPPS, dinamic light scattering and zeta potential using liposomes were used to clarify the mechanisms of action of Ctn [15-34]. All peptides were active against all yeast strains, including those resistant to antifungals. The association of fluconazole with both Ctn and Ctn[15-34], although not synergic, was able to reduce the antifungal MIC values against fluconazole-resistant C. albicans back to the susceptibility standards. Moreover, Ctn[15- 34] alone or in combination with fluconazole inhibited yeast growth after 8 hours of treatment. Ctn [15-34] inhibited biofilm formation, even against resistant strains. Spectroscopic assays showed an interaction of the peptide with the Candida membrane. Overall, Ctn and Ctn[15-34] are potential antifungal leads displaying anti-yeast activities even against clinical isolates endowed with drug resistance mechanisms. The effective peptide activity against resistant strains of pathogenic yeasts demonstrates that crotalicidin-derived peptides are promising templates to the development of new antifungals.